2020
DOI: 10.1111/jace.17391
|View full text |Cite
|
Sign up to set email alerts
|

Visible emission and energy transfer in Tb3+/Dy3+ co‐doped phosphate glasses

Abstract: In this work, we systematically study the spectroscopic properties of Tb 3+ /Dy 3+ codoped phosphate glasses in the visible spectral region and explore the sensitization role of Dy 3+ in the enhancement of visible fluorescence of Tb 3+ ions. Judd-Ofelt parameters Ω 2 and Ω 4 /Ω 6 of the phosphate glass as host for Tb 3+ are calculated as 21.60 × 10-20 cm 2 and 0.73, respectively, based on the measured spectral absorption. Multiple energy transfer (ET) routes from Dy 3+ to Tb 3+ and their efficiencies are chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Compared to other glass systems [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], the energy transfer is of special interest here. As can be seen in Figure 6 a, Tb shows almost no emission when excited with a Dy -related excitation wavelength, i.e., 452 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other glass systems [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], the energy transfer is of special interest here. As can be seen in Figure 6 a, Tb shows almost no emission when excited with a Dy -related excitation wavelength, i.e., 452 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, a larger absorption cross section (σ a ) is more conducive to light absorption. We have calculated the absorption cross sections using the following formula: 13,23 can be observed in the energy level diagram of Dy 3+ /Tb 3+ ions, as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shanghai Institute of Optics and Fine Mechanics also demonstrated visible luminescence and realized green lasing in Dy 3+ /Tb 3+ co-doped phosphate glasses. 13 It indicated that Dy 3+ ion played the role of sensitizer for the visible emission and lasing of Tb 3+ ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1. As demonstrated by Tomoya Okazaki et al,18 the absorption band centered at shorter than 210 nm (photon energy higher than 6 eV) is ascribed to the transition of Dy 3+ : 4f-4f5d that shows much higher absorption cross section23 than 4f-4f transitions 24. The UV absorption edge of Dy-silica glasses shows dependence on P/Al ratio.…”
mentioning
confidence: 84%